Disentangling Antirhea (Rubiaceae): resurrection of Guettardella and description of the new genus Achilleanthus. (23rd March 2021) - Chavez, Jayson G; Meve, Ulrich; Nürk, Nicolai M; Liede-Schumann, Sigrid
Abstract: The Palaeotropical genus Antirhea (Guettardeae, Rubiaceae) currently comprises 37 dioecious species classified into three subgenera, Antirhea, Mesocarpa and Guettardella . It has a complex taxonomic history with varying generic delineation and variable application of species names. Recent phylogenetic studies have indicated the non-monophyly of Antirhea, but the limited sampling does not allow resolution of its circumscription or nomenclatural changes to be proposed. Here, we reconcile the generic boundaries of Antirhea based on phylogenetic analyses of two nuclear (ETS, ITS) and three plastid loci ( atpB-rbcL, rps16, trnT-F ) using Bayesian, maximum likelihood and parsimony methods. Our results show that Antirhea in its current circumscription is highly polyphyletic, whereas its three subgenera are retrieved as well-supported independent clades. A new generic framework is proposed based on phylogenetic results and supported by morphological evidence. We intend to restrict Antirhea to species native to the Mascarene Islands and Madagascar, to reinstate the genus Guettardella with emended diagnostic features and to describe the new genus Achilleanthus to accommodate the species of subgenus Mesocarpa plus Guettarda glabrescens, G. hypoplasia and G. ngoyensis . As a consequence, seven new combinations in Achilleanthus and 17 new combinations in Guettardella are made.